2021
DOI: 10.3390/pharmaceutics13091368
|View full text |Cite
|
Sign up to set email alerts
|

External Model Performance Evaluation of Twelve Infliximab Population Pharmacokinetic Models in Patients with Inflammatory Bowel Disease

Abstract: Infliximab is approved for treatment of various chronic inflammatory diseases including inflammatory bowel disease (IBD). However, high variability in infliximab trough levels has been associated with diverse response rates. Model-informed precision dosing (MIPD) with population pharmacokinetic models could help to individualize infliximab dosing regimens and improve therapy. The aim of this study was to evaluate the predictive performance of published infliximab population pharmacokinetic models for IBD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Currently, there is no well‐established target of classification accuracy for MIPD approach. To the best of our knowledge, classification accuracy has only been included for model predictive performance evaluation for infliximab in Schräpel et al 32 Therefore, defining clinical relevance of these additional analysis tools still requires further investigation to facilitate the translation and appropriate use of the MIPD approaches in clinical care. Third, we also scrutinized the importance of utilizing point‐of‐care testing and the availability of covariate data on the predictive performances.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no well‐established target of classification accuracy for MIPD approach. To the best of our knowledge, classification accuracy has only been included for model predictive performance evaluation for infliximab in Schräpel et al 32 Therefore, defining clinical relevance of these additional analysis tools still requires further investigation to facilitate the translation and appropriate use of the MIPD approaches in clinical care. Third, we also scrutinized the importance of utilizing point‐of‐care testing and the availability of covariate data on the predictive performances.…”
Section: Discussionmentioning
confidence: 99%
“…The sparse concentration measurements in our study precluded the development of an original PK model. Therefore, we evaluated the usefulness of published population PK models for cisplatin in SCLC, by adopting the approach that was recently shown beneficial in informing treatment with other drugs, such as anti-infectives (vancomycin, meropenem, polymyxin B), monoclonal antibodies (infliximab, adalimumab), and imatinib, among others [25,27,28,[34][35][36][37]. In addition, we used informative priors and $PRIOR subroutine in NONMEM, which was demonstrated to produce improved predictive performance of the PK models on sparse datasets, on the population (a priori) and individual (a posteriori) level [29].…”
Section: Discussionmentioning
confidence: 99%
“…Possible errors in the sampling and infusion time documentation in the early phase could further contribute to higher bias and imprecision, since a recent study demonstrated that even 5 min inaccuracies affect the estimation of volume of distribution in central and peripheral compartment, as well as the intercompartmental clearance [42]. However, the choice of the robust predictive performance parameters (SSPB and ζ) to assess the bias and precision mitigated the outlying error values and possible data inaccuracies in the early phase [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the selected articles, only two models took ADA into account in a more mechanistic way, seeking to implement immunogenicity impact on clearance and improving model predictions [ 38 , 52 ]. In general, as shown by Schräpel et al, poor predictions are observed for ADA-positive patients compared to ADA-negative in most developed models [ 61 ]. Thus, implementation of more mechanistic models, accounting for the impact of ADA development on PK, as well as on pharmacodynamics, could improve the therapeutic management of ADA-positive patients.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%